Role of fibronectin in staphylococcal colonisation of fibrin thrombi and plastic surfaces - Valentin-Weigand, P.; Timmis, K. N.; Chhatwal, G. S. (Journal of Medical Microbiology, 1993)
Summary The adhesive glycoprotein fibronectin has been proposed as a mediator of adherence of certain gram-positive cocci to host cells and fibrin thrombi. This study compared the role of soluble and immobilised fibronectin in the adherence of coagulasenegative staphylococci (CNS) and Staphylococcus aureus to fibrin thrombi and plastic surfaces. Adherence of S. epidermidis to fibrin thrombi was significantly reduced when fibronectin was removed from the plasma used for thrombus preparation. Adherence was restored through restitution of fibronectin. S. epidermidis also adhered substantially more to plastic surface coated with fibronectin than to non-coated plastic. Increased adherence of CNS to plastic was also observed after coating with the 29-kDa N-terminal fragment of fibronectin. Soluble fibronectin did not affect the adherence of CNS to fibrin thrombi or plastic surfaces. The adherence of S. aureus to fibrin thrombi was significantly increased by the addition of soluble fibronectin, but not by incorporation of fibronectin into the clot. These results indicate that the binding of fibronectin is an important factor in the adherence of staphylococci to fibrin clots and plastic surfaces and, thus, colonisation of these surfaces. However, the two species of staphylococci seem to employ different mechanisms of fibronectin-mediated adherence: S. epidermidis interacts mainly with fibronectin incorporated in fibrin clots or immobilised on implanted synthetic materials, whereas S. aureus adheres to the fibrin matrix through binding of soluble fibronectin present in wound exudates.